MO357ACUTE KIDNEY INJURY IN HOSPITALIZED COVID-19 PATIENTS: A MULTICENTRE STUDY BY TURKISH SOCIETY OF NEPHROLOGY. (29th May 2021) - Arıkan, İzzet Hakkı; Ozturk, Savas; Tokgoz, Bulent; Dursun, Belda; Seyahi, Nurhan; Trablus, Sinan; Islam, Mahmud; Ayar, Yavuz; Gorgulu, Numan; Karadag, Serhat; Gok, Mahmut; Akcali, Esra; et al.
Abstract: Background and Aims: Acute kidney injury (AKI) is common in coronavirus disease-2019 (COVID-19) and the severity of AKI is linked to adverse outcomes. In this study, we investigated the factors associated with in-hospital outcomes among hospitalized patients with COVID-19 and AKI. Method: In this multicenter retrospective observational study, we evaluated the characteristics and in-hospital renal and patient outcomes of 578 patients with confirmed COVID-19 and AKI. Data were collected from 34 hospitals in Turkey from March 11 to June 30, 2020. AKI definition and staging were based on the Kidney Disease Improving Global Outcomes criteria. Patients with end-stage kidney disease or with a kidney transplant were excluded. Renal outcomes were identified only in discharged patients. Results: The median age of the patients was 69 years, and 60.9% were males. The most frequent comorbid conditions were hypertension (70.5%), diabetes mellitus (43.8%), and chronic kidney disease (41.5%). The proportions of AKI stages 1, 2, and 3 were 54.0%, 24.7%, and 21.3%, respectively. 291 patients (50.3%) were admitted to the intensive care unit. Renal improvement was complete in 80.7% and partial in 17% of the patients who were discharged. Renal outcomes were worse in patients with AKI stage 3 or baseline CKD. The overall in-hospital mortality in patients with AKI was 38.9%. By multivariate Cox regression analysis, age (hazard ratio [HR] [95% confidence interval (95%CI)]: 1.01 [1.0-1.03], p = 0.035], male gender (HR [95%CI]: 1.47 [1.04-2.09], p = 0.029), diabetes mellitus (HR [95%CI]: 1.51 [1.06-2.17], p = 0.022) and cerebrovascular disease (HR [95%CI]: 1.82 [1.08-3.07], p = 0.023), serum lactate dehydrogenase (greater than two-fold increase) (HR [95%CI]: 1.55 [1.05-2.30], p = 0.027) and AKI stage 2 (HR [95%CI]: 1.98 [1.25-3.14], p = 0.003) and stage 3 (HR [95%CI]: 2.25 [1.44-3.51], p = 0.0001) were independent predictors of in-hospital mortality. The in-hospital mortality rates across AKI stages by age, gender, and diabetes mellitus were shown in the Figure . Conclusion: Advanced-stage AKI is associated with extremely high mortality among hospitalized COVID-19 patients. Age, male gender, comorbidities, which are risk factors for mortality in patients with COVID-19 in the general population, are also related to in-hospital mortality in patients with AKI. Renal problems continue in a significant portion of the patients who were discharged.